The Effect of Marketing Mix on Unplanning Purchases at PT. Alfamart in Banjarmasin - Rina Rina; Apriya Santi (Hut Publication Business and Management, 2022)
This research aims to determine the effect of the marketing mix on unplanned purchase at PT. Alfamart. Explanatory research methods approach with survey techniques, the number of samples in this study were one hundred respondent's who had shopped at least twice in the PT. Alfamart. The results showed that the variable product, price, place, promotion, people, physical evidence, and process have significant effect on unplanned purchases at PT. Alfamart, and the results of the descriptive analysis states that the respondents agreed with the proposed items.